2019
DOI: 10.1093/femsyr/foz057
|View full text |Cite
|
Sign up to set email alerts
|

Impact of manganese on biofilm formation and cell morphology of Candida parapsilosis clinical isolates with different biofilm forming abilities

Abstract: The commensal species Candida parapsilosis is an emerging human pathogen that has the ability to form biofilms. In this study, we explored the impact of the divalent cations cobalt (Co2+), copper (Cu2+), iron (Fe3+), manganese (Mn2+), nickel (Ni2+) and zinc (Zn2+) on biofilm formation of clinical isolates of C. parapsilosis with no, low and high biofilm forming abilities at 30 and 37°C. All strains besides one isolate showed a concentration-dependent enhancement of biofilm formation at 30°C in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
(92 reference statements)
2
7
0
Order By: Relevance
“…This finding demonstrates the ability of BCR1 to respond to signals from the environment. In agreement with the findings of Shafeeq et al [37], and under our experimental conditions, the basal transcriptional activity of BCR1 was shown to be higher in those isolates that recovered under conditions of gingivoperiodontal disease. This condition is characterized by the imbalance of the colonizing microbiota, with a periodontopathogen predominance of the red and orange complex [38], in addition to the REDOX imbalance [39,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding demonstrates the ability of BCR1 to respond to signals from the environment. In agreement with the findings of Shafeeq et al [37], and under our experimental conditions, the basal transcriptional activity of BCR1 was shown to be higher in those isolates that recovered under conditions of gingivoperiodontal disease. This condition is characterized by the imbalance of the colonizing microbiota, with a periodontopathogen predominance of the red and orange complex [38], in addition to the REDOX imbalance [39,40].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Shafeeq and his group [37] published in 2019 a study in which they demonstrate the property of BCR1 to respond to high levels of manganese, which led to the formation of biofilm in strains previously defined as nonforming and low biofilm-forming. This finding demonstrates the ability of BCR1 to respond to signals from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, deletion of the multicopper oxidase gene CaFET34, but not deletion of CaFET33, significantly attenuated the filamentous growth of C. albicans (25). In the case of C. parapsilosis, Shafeeq et al showed Mn ϩϩ -dependent biofilm formation through the activity of the biofilm regulator BCR1 (41). All these data prompted us to investigate whether a similar effect occurs in C. parapsilosis.…”
Section: Fig 10mentioning
confidence: 95%
“…The adherence ability of Staphylococcus epidermidis is enhanced in low concentrations of magnesium [42]. In C. parapsilosis, an increase in Mn 2+ , with a maximum at 2 mM, significantly induced biofilm formation [43]. Moreover, different metal ions can suppress or enhance C. albicans and C. tropicalis biofilm formation.…”
Section: Discussionmentioning
confidence: 99%